The Relationship Between Risk Factors and Cervical Cancer Stage at the Gynecologic Oncology Polyclinic of RSUDZA - Alfarah, Tasya Dafa; Ishak, Saifuddin; Hasanuddin (Surgical Residency Program Syiah Kuala University, 2025)
Introduction: Cervical cancer remains a major global health problem, particularly in developing countries such as Indonesia. Most deaths from cervical cancer are caused by delayed diagnosis, resulting in patients being detected at advanced stages. Although many studies examine risk factors for cervical cancer incidence, studies linking these same factors to the stage at diagnosis are limited representing a research gap this study addresses. This study aimed to determine the relationship between five cervical cancer risk factors and cancer stage at diagnosis at the Gynecologic Oncology Polyclinic of RSUDZA Banda Aceh. Methods: Observational analytic cross-sectional study using secondary data (medical records). A non-probability total sampling technique was applied (N = 54; n = 52 after exclusion). Bivariate analysis used Fisher's Exact and Mann–Whitney tests (95% CI, α = 0.05). Ethical approval was obtained from the Health Research Ethics Committee FK USK RSUDZA (No. 221/EA/FK-RSUDZA/2021, 26 July 2021). Results: No significant relationship was found between age at marriage (p = 1.000), parity (p = 0.595), education (p = 0.894), income (p = 0.102), or oral contraceptive use (p = 1.000) and cervical cancer stage. Conclusion: Stage at diagnosis is more strongly determined by access to and uptake of early-detection services and health-seeking behavior than by these demographic or reproductive risk factors. Strengthening community-based screening (VIA, Pap smear) and HPV vaccination is essential to reduce the proportion of patients diagnosed at advanced stages.